Moğolca-Azerbaycan Türkçesi söz denklikleri - Kabaca, Sevinc (My University, 2022)
Bu tezde Azerbaycan Türkçesindeki Moğolca söz denklikleri incelenmiştir. Çalışmada Azerbaycan Dilinin İzahlı Lugati, Azerbaycan Dilinin Dialektoloji Lugati, F.D. Lessing’in Mongolian-English Dictionary’si ana kaynak olarak kullanılmıştır. Araştırma sonucunda ortak birçok kelime tespit edilse de çalışma 100 kelime ile sınırlı tutulmuştur. Çalışmada tespit edilen 100 kelime ve bu kelimelerin Azerbaycan Türkçesindeki bütün türevleri verilmiştir. Saptanan kelimeler Azerbaycan Dilinin İzahlı Lügati’nde ve Azerbaycan Dilinin Dialektoloji Lügati’de geçen sözcüklerdir. Bulunan her kelime üzerinde ayrıca inceleme yapılmış, Azerbaycan Türkçesi, Moğolca, Tarihi Türk dilleri, çağdaş Türk lehçeleri ve Anadolu ağızlarındaki kullanım şekilleri verilmiştir. Çalışma sonucunda saptanan sözcüklerin Moğolca, Azerbaycan Türkçesi ve Türkiye Türkçesinde kavramsal dizinleri hazırlanmıştır.

Turkish Mongolian lexical equivalences in Azerbaijani have been examined in this thesis. In the study, the Explained Lugati of the Azerbaijani Language, The Dialectology of the Azerbaijani Language Lugati, F.D. Lessing's Mongolian-English Dictionary was used as the main source. Although many common words were identified as a result of the research, the study was limited to 100 words. The 100 words identified in the study and all the derivatives of these words in Azerbaijani Turkish are given. The identified words are the words in the Explained Language of the Azerbaijani Language and the words in the Dialectological Language of the Azerbaijani Language. Turkish Mongolian, Historical Turkish languages, contemporary Turkish Polishes and Anatolian dialects are also examined on each word found and usage patterns in Azerbaijani Turkish, Mongolian, Historical Turkic languages are given. Turkish Mongolian Turkish, Azerbaijani Turkish and Turkish conceptual indexes of the words identified as a result of the study were prepared.
Keywords: Azerbaijani language; Azeri dili; Moğol dili; Moğolca Moğolca; Mongolian language; Turkic languages; Turkish; Türk dili; Türkçe